"I'm concerned": A multi-site assessment of emergency medicine resident speaking up behaviors. Issue 5 (October 2022) - Feldman, Nicola; Volz, Nico; Snow, Tim; Wong, Lillian; Hock, Sara M; Barnes, David K; Bentley, Suzanne
Introduction: According to the Institute of Medicine, 98, 000 annual deaths are caused by preventable errors. Speaking up about patient safety or professionalism concerns when they arise allows medical staff to move from bystanders to active participants in the prevention of patient harm. This study assesses the current climate around speaking up for patient safety and unprofessional behavior by Emergency Medicine (EM) resident physicians and compares it to previously published data from other specialties. Methods: A multi-site, descriptive, cross-sectional design was utilized based on previously published Speaking Up Climate Safety and Professionalism Scales. EM residents at 3 programs in the United States were surveyed, and their responses were compared to previously published responses from other specialties. Results: 102 residents from 3 EM residency programs responded to the survey, yielding a response rate of 54.3%. Responses on the survey fell close to the neutral response (3 on a 5-point Likert scale) on all measures, indicating opportunity for improvement. However, EM responses were significantly more favorable than responses from other specialties on several questions. Conclusion: This assessment demonstrates room for improvement on speaking up behaviors among EM residents but also suggests that unique features of EM may contribute to a relatively more positive speaking up climate compared to other specialties, which may inform strategies to increase speaking up behaviors. For example, deliberate practice of situations requiring strong teamwork and strategies to reduce traditional hierarchies may help emulate the climate that tends to occur organically in EM.